What's in a Name? - Saku Aura; Gregory D. Hess (Center for Economic Studies and ifo Institute (CESifo), 2004)
Plenty. This paper analyzes two broad questions: Does your first name matter? And how did you get your first name anyway? Using data from the National Opinion Research Centers (NORC's) General Social Survey, including access to respondents first names from the 1994 and 2002 surveys, we extract the important first name features (FNF), e.g. popularity, number of syllables, phonetic features, Scrabble score, blackness (i.e. the fraction of people with that name who are black), etc ... We then explore whether these first name features are useful explanatory factors of a respondent's exogenous background factors (sex, race, parents' education, etc...) and lifetime outcomes (e.g. financial status, occupational prestige, perceived social class, education, happiness, and whether they became a parent before 25). We find that first name features on their own do have significant predictive power for a number of these lifetime outcomes, even after controlling for a myriad of exogenous background factors. We find evidence that first name features are independent predictors of lifetime outcomes that are likely related to labor productivity such as education, happiness and early fertility. Importantly, however, we also find evidence based on the differential impacts of gender and race on the blackness of a name and its popularity that suggest that discrimination may also be a factor.
Keywords: D10; J10; J70; 330; names; identity; discrimination